Variations on an Exegetical Theme: Tafsīr Foundations in the Malay World - Peter G. Riddell (Studia Islamika, 2014)
The field of tafsīr al-Qur’ān in Malay has attracted increasing scholarly attention in recent decades. The volume of commentaries has grown exponentially in the 20th century. Prior to that, Qur’anic exegesis in Malay was sporadic and varied. This paper will consider pioneering efforts by Malay commentators on the Qur’an, focusing on three key sets of materials. First, we will consider the earliest surviving fragments of tafsīr in Malay. Second, we will examine Tarjumān al-Mustafīd by ‘Abd al-Ra’ūf of Singkel, the first known commentary in Malay upon the whole  Qur’an, written in the late 17th century and subsequently widely disseminated throughout the Malay world. Third, we will focus upon the early 20th century commentary by Muḥammad Sa‘īd bin ‘Umar of Kedah, regarded by many as the second commentary in Malay upon the whole Qur’an.DOI: 10.15408/sdi.v21i2.1072